Overspecified references: An experiment on lexical acquisition in a virtual environment. (August 2015) - Luccioni, Alexandra; Benotti, Luciana; Landragin, Frédéric
Highlights: We study the utility of overspecification in language learning. We compare two groups of learners receiving different degrees of specification. Giving more specification in practise exercises improves lexical acquisition rates. Overspecification affects the design of language learning materials and software. Abstract: This study explores the role of quantity of information on vocabulary acquisition in a virtual world. Previous studies have shown that, although it makes interpretation more lengthy, speakers include more information in their referring expressions than is strictly necessary to identify an object – they overspecify . We aim to study the impact of this kind of overspecification on the acquisition of new lexemes in a foreign language. Our hypothesis is that using overspecified expressions during the practice of recently acquired vocabulary will help learners to better remember the lexemes and to exploit them more efficiently later on. In this paper, we describe an experimental study designed to evaluate this hypothesis, comparing two groups of learners who received overspecified and minimally specified referring expressions while practising newly acquired lexemes in the context of a language learning game in Russian. The game is situated in a virtual environment and the interaction is similar to that of a video game. Our results, based on experimental data from participants' performance as well as a post-experiment questionnaire, support the claim that overspecification improves lexical acquisition rates compared to minimal specification. Some pedagogical suggestions are provided for the design of referring expression generation algorithms in Technology-Enhanced Language Learning (TELL) and Computer Assisted Language Learning (CALL) Systems.